Ethos, Logos and Pathos in the Persuasion of the Sides of the Civil War in the Game Elder Scrolls V: Skyrim - Känsäkangas, Teemu (My University, 2024)
This thesis deals with persuasion in video games, specifically in Elder Scrolls V: Skyrim, from a lin guistic perspective. The aim of the study was to look at how persuasion manifests itself in some of the scenes of dialogue in Skyrim, how it relates to the Aristotelian modes of persuasion, and how player agency affects the persuasion that the player is subjected to. The method of analysis used in this study is a method utilizing close reading, adapted to a video game study. The adaptation of the methodology is based on the previous work of Higgins and Walker. The results show that the dialogue in Skyrim utilizes all persuasive techniques analyzed in this study. The language of persuasion experienced by the player affects their view on the character based on the Aristotelian modes of persuasion. The re searcher suggests that since persuasion is clearly present in video games, they need to be researched further to understand the effectiveness of persuasion that happens in fictional settings. The researcher also suggests further changes to the methodology of the study and proposes that it would be beneficial to include surveys on persuasiveness of the characters for players of video games.
Keywords: persuasion, ethos, logos, pathos, game studies, persuasive technique, mode of persuasion